2019
DOI: 10.3389/fmars.2019.00330
|View full text |Cite
|
Sign up to set email alerts
|

Ocean Observing and the Blue Economy

Abstract: Sustained ocean observations provide an essential input to ocean scientific research. They also support a wide range of societal and economic benefits related to safety; operational efficiency; and regulation of activities around, on, in, and under seas and the ocean. The ocean economy is large and diverse, accounting for around US$1.5 trillion of global gross value-added economic activity. This is projected to more than double by 2030. Delivering this growth in economic activity is dependent on ocean observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(33 citation statements)
references
References 1 publication
0
30
0
3
Order By: Relevance
“…Most activities related to the economic exploitation of the maritime environment carried out by humans do not conform to the notions of a "BE" since this economic exploitation does not often focus on a sustainable maritime environment (Rayner et al, 2019). Similarly, it has been found that the synergies, con icts between sectors, and political decisions could in uence the sustainable growth of the BE in highly contested regions such as the North Sea basin.…”
Section: Discussionmentioning
confidence: 99%
“…Most activities related to the economic exploitation of the maritime environment carried out by humans do not conform to the notions of a "BE" since this economic exploitation does not often focus on a sustainable maritime environment (Rayner et al, 2019). Similarly, it has been found that the synergies, con icts between sectors, and political decisions could in uence the sustainable growth of the BE in highly contested regions such as the North Sea basin.…”
Section: Discussionmentioning
confidence: 99%
“…Marine biotechnology is a niche within the oceanbased industries. As this is a growing field, it is projected that in 2030 many ocean-based industries will outperform the growth of the global economy as a whole, providing approximately 40 million full-time equivalent jobs (Rayner et al, 2019). Besides creating new jobs, the development of marine biotechnology can contribute to the existing employment structures by diversification of additional income for fishermen or aquaculture specialists.…”
Section: Bioeconomymentioning
confidence: 99%
“…(iv) There is a need to develop strategies for showcasing individual expertise, such as the creation of open access repositories of experts and their contacts. (v) Finally, there is a need to sustain the investment into ocean observations that provide evidence of regulatory compliance and support the valuation of natural assets and ecosystem services (Rayner et al, 2019). Open science, also through full access to research publications (embraced by Plan S and supported by the EC 3 ) and access to data are of key importance here, enabling fair access to public knowledge.…”
Section: Bioeconomymentioning
confidence: 99%
“…Stemming from these emerging needs, Marine Observing systems (MOs) have spread globally as integrated observing and experimenting infrastructures able to monitor oceanographic variables and to collect high-resolution data in selected marine regions to assess their state both in coastal and offshore areas (Crise et al, 2018;Rayner et al, 2019). MOs, although essential for generating knowledge and supporting evidence-based decisions (GOOS, 2019), do not provide a truly holistic view of the marine ecosystems, since they mostly address the oceanographic processes and barely include the ecological ones.…”
Section: Introductionmentioning
confidence: 99%